Statistical analysis of the maternal death rate at the Ebonyi State University Teaching Hospital, Abakaliki, for the year ending 31 December 2007 - Uchechukwu M. Okeh (AOSIS, 2009)
Background: The maternal mortality rate in developing countries, such as Nigeria, remains relatively high, with the causes being multidimensional. The unbooked primigravidae with severe pre-eclampsia/eclampsia constitute a high risk group. Method: The data from the case notes of all the maternal deaths that occurred at the Ebonyi State University Teaching Hospital, Abakaliki, between 1 January and 31 December 2007 form the basis of this study. The case notes relating to all such deaths were stored in the office of the Head of the Department of Obstetrics and Gynaecology when the deaths occurred. Information was extracted from the case files at the end of 2007. Data relating to the total number of deliveries were obtained from the registers kept in the labour and isolation wards. Results: Of the 45 maternal deaths recorded, 40 (88.9%) were found to have occurred among the unbooked and 5 (11%) among the booked mothers, constituting a maternal mortality ratio (MMR) of 23 121.4 and 339.7 per 100 000 deliveries respectively. The combined mortality ratio was 2 735.6 per 100 000 deliveries. Fifteen (37.5%) unbooked primigravidae were found to have died of severe pre-eclampsia/eclampsia. A total of 1 645 mothers were noted to have delivered babies, of whom 1 472(89.5%) were booked, and 173 (10.5%) unbooked, with the hospital. Conclusion: Severe pre-eclampsia/eclampsia, haemorrhaging and sepsis were the major causes of death. A high maternal mortality rate was found to be common among the unbooked primigravidae, who are known usually to present late with pre-eclampsia/eclampsia. More research into the causes and management of pre-eclampsia/eclampsia is needed to reduce the high maternal death rate associated with it. The lack of antenatal care is also a high risk factor for maternal death.